Some Synthetic Phytotoxins Structurally Related to Rhynchosporoside - Beltran, J. Pio (1980)
The (2-O)α-d-glucopyranoside of 1,2-propanediol and [U-(14)C]glucose were used as substrates in a reaction with almond β-glucosidase, which resulted in the production of some (2-O)α-d-oligoglucosides of 1,2-propanediol. As its substrate, the β-glucosidase preferred the glucoside isomer that rotates plane-polarized light to the right. Some of the glucosides produced in the enzymic reaction mixture possessed host selective toxin activity. It appears that the biological activity of the toxin is not dependent on the nature of the glycosidic linkage with the aglycone.